Entrepreneurship Resilience: Can Psychological Traits of Entrepreneurial Intention Support Overcoming Entrepreneurial Failure? - Zhao, Hong; Wibowo, Ardy (Frontiers in Psychology, 2021)
Entrepreneur failure (EF) is very likely to occur due to aspects beyond an entrepreneur's control, even if planning and calculations have been completed before then. This research proposes a framework to illustrate how entrepreneurs cope with failure, based on the psychological characteristics that lead them to become entrepreneurs. This research considered entrepreneurial self-efficacy and internal locus of controls to measure the perceived learning from failure and recovery capability that able to create the after-failure outcomes, which are continuance entrepreneur engagement and new opportunity recognition. SmartPLS 3 was used to calculate and evaluate the 146 data from the online questionnaire survey. The result shows that the psychological characteristics represented by self-efficacy and internal locus of control able to influence the entrepreneur's willingness to learn from failure and increase their recovery capabilities. In the end, resulting in their willingness to continue to engage in entrepreneurship and help them to recognize a new opportunity. However, recovery capability will not be influenced by self-efficacy and will not influence the new opportunity recognition because the recovery capability may vary among the entrepreneurs depends on many factors.